2019
DOI: 10.3758/s13415-019-00710-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the opioid system in decision making and cognitive control: A review

Abstract: The opioid system regulates affective processing, including pain, pleasure, and reward. Restricting the role of this system to hedonic modulation may be an underestimation, however. Opioid receptors are distributed widely in the human brain, including the more Bcognitive^regions in the frontal and parietal lobes. Nonhuman animal research points to opioid modulation of cognitive and decision-making processes. We review emerging evidence on whether acute opioid drug modulation in healthy humans can influence cog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 228 publications
(256 reference statements)
0
43
0
Order By: Relevance
“…We observed greater opioid release in higher fit participants after aerobic exercise in ventral and dorsal striatum, left hippocampus, left thalamus, insular cortex, somatosensory cortex, temporal areas, and orbitofrontal cortex. MORs in these regions are closely involved in processing both nociceptive and hedonic signals [21,48] as well as modulating decision making and cognitive control [49]. We found that higher fit participants experienced greater improvements in mood following the aerobic exercise.…”
Section: Discussionmentioning
confidence: 89%
“…We observed greater opioid release in higher fit participants after aerobic exercise in ventral and dorsal striatum, left hippocampus, left thalamus, insular cortex, somatosensory cortex, temporal areas, and orbitofrontal cortex. MORs in these regions are closely involved in processing both nociceptive and hedonic signals [21,48] as well as modulating decision making and cognitive control [49]. We found that higher fit participants experienced greater improvements in mood following the aerobic exercise.…”
Section: Discussionmentioning
confidence: 89%
“…heroin) exert their analgesic and addictive effects primarily through the µ-opioid receptor. 7 , 62 The binding of opioids in the limbic circuitry plays a critical role in analgesia, 32 learning and value-based decision making, 63 , 64 and hedonic processes. 65 , 66 For example, the infusion of naloxone, a µ-opioid receptor antagonist, into the basolateral amygdala decreases lever pressing for food in deprived rodents previously trained to associate lever pressing with delivery of a sucrose reward.…”
Section: Discussionmentioning
confidence: 99%
“…But reason, says Hume ( 1739 ), is the slave of the passions. Supporting Hume, latter-day empirical studies indicate that reasoning is an inherently emotional process [see van Steenbergen et al ( 2019 )].…”
Section: Discussionmentioning
confidence: 99%